Analisis Pengaruh Return On Equity, Debt To Total Asset Ratio, Debt To Equity Ratio, Earning Per Share Dan Price Earning Ratio Pada Harga Saham - Semilir, Khansa Pandan; Mustikasari, Elia (Owner : Riset dan Jurnal Akuntansi, 2024)
One of the analytical techniques that investors can apply to understand a company's financial condition is fundamental analysis using financial ratios in financial statements. The results of investors' analysis of the company's financial condition will determine investors' interest in investing as reflected in the company's stock price. The COVID-19 pandemic in Indonesia had a significant impact on the operations of manufacturing companies. In this regard, this study aims to examine the effect of ROE, DAR, DER, EPS, and PER on the stock prices of manufacturing companies listed on the Indonesia Stock Exchange (IDX) from 2020 to 2022. This study used a sample of 286 companies, which were analyzed using multiple linear regression with the help of SPSS version 20 software. Based on the results of this study, it was determined that ROE had a positive effect on stock prices, DAR had a negative effect on stock prices, and EPS had a positive effect on stock prices. Meanwhile, two other financial ratios, namely DER and PER, have no effect on stock prices